2019
DOI: 10.1021/acsinfecdis.9b00213
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Simplification of Carolacton Enables Chemical Genetic Studies in Streptococcus mutans

Abstract: Understanding the broader biological impact of carolacton, a macrolactone natural product, has been ongoing for the past decade. Multiple studies have shown connections to regulatory systems, acid tolerance mechanisms, biofilm formation, and recently folate dehydrogenase (FolD). Progress elucidating the cause of biofilm-specific activity in Streptococcus mutans has been limited due to low-throughput analyses of carolacton-treated cells. We disclose the discovery of a simplified carolacton-inspired analog that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“… 16 This finding also showed the importance of chain length and, in a follow up paper in 2019, we were able to simplify the carolacton side chain while oversaturating the carolacton macrocycle to produce a drastically simplified analog, (+)-2 ( 3 ).This analog not only maintained activity with an IC 50 of 44 μM but also allowed for the first observance of a minimum inhibitory concentration (MIC) value for any compound structurally related to carolacton at 250 μM. 17 This analog effectuated the preliminary screening of S. mutans mutants, aiding in the identification of a carbon catabolite control protein (Ccpa) as the putative target of 3 . Hence, this analog provided an additional tool for which further biological data could be garnered in future assays.…”
Section: Isolation To Synthesis and Beyondmentioning
confidence: 85%
“… 16 This finding also showed the importance of chain length and, in a follow up paper in 2019, we were able to simplify the carolacton side chain while oversaturating the carolacton macrocycle to produce a drastically simplified analog, (+)-2 ( 3 ).This analog not only maintained activity with an IC 50 of 44 μM but also allowed for the first observance of a minimum inhibitory concentration (MIC) value for any compound structurally related to carolacton at 250 μM. 17 This analog effectuated the preliminary screening of S. mutans mutants, aiding in the identification of a carbon catabolite control protein (Ccpa) as the putative target of 3 . Hence, this analog provided an additional tool for which further biological data could be garnered in future assays.…”
Section: Isolation To Synthesis and Beyondmentioning
confidence: 85%
“…A natural product Carolacton ( 14 ) (Figure 4), is a macrolide keto‐carboxylic acid produced by the myxobacterium Sorangium cellulosum with a wide biological profile. The comprehensive evaluations have shown an association of 14 with regulatory systems, acid tolerance mechanism, biofilm formation, and folate dehydrogenase [85–86] . It acts as a promising inhibitor of biofilm formation in the human pathogen Streptococcus mutant , a growth inhibitor of S. pneumonia , and an inhibitor of efflux pump mutant Escherichia coli ΔtolC [87–89] …”
Section: Natural Products and Their Derivatives With Activity Against Sars‐cov‐2mentioning
confidence: 99%
“…For our second generation, we aimed to make eight analogs that were designed to have a flexible sidechain by removing the aryl bioisostere (27) (Scheme 4). 22 Once again, the diverted synthesis strategy was utilized to access these analogs, and a simplified structure, coined 'analog 2', was identified. Structurally, carolacton and analog 2 shared key features such as the terminal carboxylic acid and length of the sidechain.…”
Section: Syn Lettmentioning
confidence: 99%
“…Through the investigation, we discovered that ΔccpA was not susceptible to analog 2. 22 This gene codes for carbon catabolite protein A, CcpA, and is responsible for the regulation of EPS formation, cell attachment, acetate metabolism branch-chain amino acid synthesis, oxidative stress tolerance, and other mechanisms tied to the acid tolerance response of S. mutans. In 2014, a transcriptomic screen completed by Sudhakar et al, showed that CcpA was one of seven transcriptional regulators to be highly coordinated to carolacton's biological activity.…”
Section: Account Syn Lettmentioning
confidence: 99%
See 1 more Smart Citation